Antisense to LOX-1 Inhibits Oxidized LDL–Mediated Upregulation of Monocyte Chemoattractant Protein-1 and Monocyte Adhesion to Human Coronary Artery Endothelial Cells - Dayuan Li; Jawahar L. Mehta (2000)
Background —We have recently demonstrated a lectin-like receptor for oxidized (ox)-LDL (LOX-1) in human coronary artery endothelial cells (HCAECs). This receptor is upregulated by ox-LDL. The present study examined the significance of LOX-1 in monocyte adhesion to HCAECs and endothelial injury in response to ox-LDL. Methods and Results —HCAECs were incubated in the presence of antisense oligodeoxynucleotides to the 5′-coding sequence of the human LOX-1 gene (0.5 μm/L). Basal LOX-1 mRNA and protein were suppressed by antisense LOX-1. Ox-LDL–mediated upregulation of LOX-1 was also suppressed by antisense LOX-1. Incubation of HCAECs with ox-LDL (40 μg/mL) for 24 hours markedly increased monocyte chemoattractant protein-1 (MCP-1) mRNA and protein expression as well as monocyte adhesion to HCAECs ( P <0.01). After 48 hours of preincubation of HCAECs with antisense LOX-1, ox-LDL–mediated upregulation of MCP-1 and monocyte adhesion to HCAECs both were suppressed ( P <0.01), whereas sense LOX-1 had no effect. Whereas antisense or sense LOX-1 alone (both 0.5 nmol/L) did not injure the cells, antisense LOX-1, but not sense LOX-1, reduced ox-LDL–mediated HCAEC injury, determined as LDH release ( P <0.01). Activation of mitogen-activated protein kinase (MAPK) may play a critical role in signal transduction in ox-LDL–mediated alteration in MCP-1 expression, since antisense LOX-1, but not the sense LOX-1, completely inhibited the ox-LDL–induced MAPK activation. Conclusions —These observations with the first use of a specific antisense to human LOX-1 mRNA suggest that LOX-1 is a key factor in ox-LDL–mediated monocyte adhesion to HCAECs.